Nos domínios de Terceira Vigília: criação literária e edição crítico-genética de romance inédito de Dyonelio Machado - Raabe, Camilo Mattar (2020)
The present doctoral dissertation aims to study the process of literary creation by Dyonelio Machado, starting from his own conceptions – from personal testimonies, from his fiction, from his intellectual formation and essay production, in addition to diverse primary sources. The knowledge thus obtained is then used to base the critical-genetic edition of the manuscript of Terceira Vigília, an unpublished novel by the writer, present in the Dyonelio Machado Estate at DELFOS – PUCRS, a documentation and cultural memory space. Publishing difficulties caused by the author’s political leftist performance, as well as by the theme and style of his writings, were responsible for a period of twenty years of ostracism in his life. Terceira Vigília, conceived between 1966 and 1980, reflects Dyonelio Machado’s thoughts on writing without prospects of ever publishing and on what he called “the book industry”. Such dialogue between life, personal conceptions and fiction is related to Dyonelio's ideas about literary creation, which are polarized between sublimation, a concept derived from his training as a psychiatrist and psychoanalysis student, and literature as a reflection of reality and an instrument of action influenced by his Marxist ideology. The manuscript, despite being finished, has several variants, which is why I propose to present the textual fixation in parallel to a fac-similar edition of the document, which will include an apparatus of notes and an essay, verifying and exploring the process of creation of the novel in relation to its author's own conceptions on the subject.